1999
DOI: 10.1007/s004180050403
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor ontogenesis in rat liver

Abstract: Vitamin D through its receptor (VDR) plays a major role in bone mineral metabolism. However, VDR is also present in a variety of cell lines as well as in numerous tissues, suggesting other functions of the hormone beyond bone metabolism and mineral homeostasis. At the liver level, it has been shown that vitamin D induces numerous changes (i.e. enzyme activity level, stimulation of some metabolic pathways and stimulation of the normal liver recovery after partial hepatectomy). However, some works did not find V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…Although VDR levels in liver might be low, it has been revealed recently that VDR is present in human liver [9,33]; as well as fetal, neonatal, and adult rat liver [34]. Furthermore, the level of VDR is much higher (>20-fold) in mouse than in human or rat hepatocytes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although VDR levels in liver might be low, it has been revealed recently that VDR is present in human liver [9,33]; as well as fetal, neonatal, and adult rat liver [34]. Furthermore, the level of VDR is much higher (>20-fold) in mouse than in human or rat hepatocytes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this work, cells were treated with a range of concentrations of 1␣,25-(OH) 2 D 3 (0.1-100 nM) reflecting the blood level in the normal adult (19 -190 nM). Although it was considered in the past that VDR could be absent or expressed at very low level in the liver, it was recently demonstrated that this receptor is present in fetal, neonatal, and adult rat liver by RT-PCR and immunohistochemistry (38). Control experiments using the inducible expression of fructose-1,6-bisphosphatase, previously shown to be controlled by VDR (31), have clearly shown that VDR was expressed and activated in our cultures after treatment with 1␣,25-(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In the classical vitamin D-responsive organs, including the intestine, bone, kidney, and parathyroid gland, vitamin D 3 -activated VDR plays a central role in the regulation of calcium and phosphate homeostasis, bone mineralization, inhibition of cell growth, and parathyroid hormone synthesis (3,7). VDR is also expressed in many other nonclassical vitamin Dresponsive organs, including the liver (8,9).…”
Section: Introductionmentioning
confidence: 99%